Hypophosphatasia - Asmaa S. AbuMaziad; Gabrielle C. Milillo (Annals of Internal Medicine: Clinical Cases)
Hypophosphatasia is a significantly heterogeneous disease caused by loss of function mutations in the alkaline phosphatase gene. Hypophosphatasia can manifest with dental and skeletal issues from birth to adulthood. This disease can be missed and underdiagnosed; therefore, it is important for clinicians to maintain a high index of suspicion for unexplained skeletal and dentition abnormalities.